Aclimatação de Cereus jamacaru dc. em diferentes substratos e níveis de irrigação propagado sexuadamente por cultivo in vitro.n vitro. - Cassimiro, Carlos Alberto Lins. (2022)
The phytogeographic domain of the Caatinga can be characterized by a low annual rainfall. However, this vegetation is quite diverse, and includes representatives of several global biomes, in addition to the vegetation locally known as Caatinga. In the context of the Caatinga biome, the botanical family Cactaceae is well adapted and distributed with 39 genera and 260 species. In addition, cacti have a great diversity of functions, from ecological, economic, cultural and nutritional, contributing in a broad way to the socio-environmental relations in the Brazilian semiarid region. Several botanical families are used in commercial exploitation, with regard to ornamental plants, it is possible to highlight the cacti, which are physiologically compatible with arid and semi-arid environments. Therefore, this work aimed to evaluate the acclimatization and vegetative development of mandacaru plants (Cereus jamacaru DC.) plants under different types of substrates and irrigation levels. The plants were cultivated in the in vitro Plant Cultivation Laboratory, located at the INSA Experimental Station, (Campina Grande, Brazil). The experiment was carried out in a completely randomized design in a 4 x 2 factorial scheme (substrate x irrigation level), with six replications, each one consisting of a pot with one plant. The plants were evaluated monthly for stem height and diameter and after six months of cultivation, and stem fresh mass, root fresh mass, stem dry mass, root dry mass and total mass, root length were also evaluated. and photosynthetic pigments. In this work, it was possible to observe that the use of commercial organic substrate (Terraplan®), together with irrigation with 100% of the field capacity provided once a week, are the best conditions for the cultivation of mandacaru, since they produced taller plants, with greater accumulation of biomass and higher growth rate.